Antibacterial Activity and Polyphenols Content of Methanolic Extract of Sapindus Rarak - Murni, Asmara; Rohman, Aufur; Angkawijaya, Artik Elisa; Santoso, Shella Permatasari (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2023)
The study focused on the methanolic extract of lerak fruit (Sapindus rarak DC.). The effect of varying extraction time and temperature on the polyphenols content of lerak extract was evaluated, that is by determining the total phenolic content (TPC), total flavonoid content (TFC), and total saponin content (TSC). The increasing extraction temperature from 30°C to 70°C was found to give increase in TPC from 172 mg GAE/100 mg to 246 mg GAE/100 mg, further increase of extraction temperature to 90°C results in the decrease of TPC. Similar effect was also observed in TFC, where TFC was found to increase as the extraction temperature was increased to 70°C, with TFC of 79 mg QE/100 mg. TSC of lerak fruit extract at 70°C was found to be 17.6 mg/100 g. Antibacterial activity assay on the lerak fruit extract shows the potential inhibitory activity of the extract on the growth of Escherichia coli and Staphylococcus aureus, wherein 95% inhibition efficiency can be achieved after the incubation of the bacteria in media containing 15 wt.% of the extract. The more prominent inhibitory effect of the extract was shown against Escherichia coli than Staphylococcus aureus. Collectively, the results of this study has demonstrated the potential of lerak fruit extract as natural antibacterial agent with foaming ability, which can be used as detergent additive.